1999
DOI: 10.1512/iumj.1999.48.1639
|View full text |Cite
|
Sign up to set email alerts
|

The Toeplitz algebra of a Hilbert bimodule

Abstract: Abstract. Suppose a C * -algebra A acts by adjointable operators on a Hilbert A-module X. Pimsner constructed a C * -algebra OX which includes, for particular choices of X, crossed products of A by Z, the Cuntz algebras On, and the Cuntz-Krieger algebras OB. Here we analyse the representations of the corresponding Toeplitz algebra. One consequence is a uniqueness theorem for the Toeplitz-Cuntz-Krieger algebras of directed graphs, which includes Cuntz's uniqueness theorem for O∞.A Hilbert bimodule X over a C * … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
170
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(172 citation statements)
references
References 19 publications
2
170
0
Order By: Relevance
“…https://doi.org/10.1017/S1446788700036168 354 David W. Kribs and Baruch Solel [10] This establishes part (i) of the definition. For (ii), suppose (e, w') e E(n) 1 …”
Section: \E W)) = R E(n) (E W(n)) = R E (E) = M°(r E (E)) = M°(r Eimentioning
confidence: 69%
See 1 more Smart Citation
“…https://doi.org/10.1017/S1446788700036168 354 David W. Kribs and Baruch Solel [10] This establishes part (i) of the definition. For (ii), suppose (e, w') e E(n) 1 …”
Section: \E W)) = R E(n) (E W(n)) = R E (E) = M°(r E (E)) = M°(r Eimentioning
confidence: 69%
“…In fact, the *-homomorphism nft determined by the left regular representation is a *-isomorphism of T{E) onto use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S1446788700036168 the C*-algebra generated by the operators {L e } [10,25]. Thus, for our purposes, we may identify the algebra T ( £ ) with this faithful representation n P , L (T(E)).…”
Section: If S(v) ^ R(w)mentioning
confidence: 99%
“…For any a ∈ A, we define π ∞ (a) ∈ L(F X ) to be the diagonal operator with ϕ X (c) ⊗ id n−1 at its X ⊗n -th entry. It is easy to verify that (π ∞ , t ∞ ) is a representation of X which is called the Fock representation of X. Fowler and Raeburn [19] (resp. Katsura [32]) have shown that the C * -algebra…”
Section: 5mentioning
confidence: 99%
“…If R = E 0 reg , then a Cuntz-Krieger (E, R)-family is the same as a Cuntz-Krieger E-family and C * (E, R) = C * (E). If R = ∅, then C * (E, R) is the Toeplitz algebra T (E) defined in [8,Theorem 4.1]. We will call a Cuntz-Krieger (E, ∅)-family a Toeplitz-Cuntz-Krieger E-family.…”
Section: Preliminariesmentioning
confidence: 99%